Atom-probe tomography of surface oxides and oxidized grain boundaries in alloys from nuclear reactors - Kruska, K; Saxey, D; Terachi, T; Yamada, T; Chou, P; Calonne, O; Fournier, L; Smith, G; Lozano-Perez, S (2013)
The preparation of site-specific atom-probe tomography (APT) samples containing localized features has become possible with the use of focused ion beams (FIBs). This technique was used to achieve the analysis of surface oxides and oxidized grain boundaries in this paper. Transmission electron microscopy (TEM), providing microstructural and chemical characterization of the same features, has also been used, revealing crucial additional information. The study of grain boundary oxidation in stainless steels and nickel-based alloys is required in order to understand the mechanisms controlling stress corrosion cracking in nuclear reactors. Samples oxidized under simulated pressurized water reactor primary water conditions were used, and FIB lift-out TEM and APT specimens containing the same oxidized grain boundary were prepared and fully characterized. The results from both techniques were found fully consistent and complementary. Chromium-rich spinel oxides grew at the surface and into the bulk material, along grain boundaries. Nickel was rejected from the oxides and accumulated ahead of the oxidation front. Lithium, which was present in small quantities in the aqueous environment during oxidation, was incorporated in the oxide. All phases were accurately quantified and the effect of different experimental parameters were analysed. © 2013 Materials Research Society.